Características e desfechos de pacientes com Covid-19 internados em um hospital de referência em cardiopneumologia - Farias, Thaisa Adrielly Ribeiro (2023)
INTRODUCTION: In December 2019, the world was surprised by the outbreak of a new viral infection. Initially, it was reported in the city of Wuhan, China, with the appearance of several cases of acute pneumonia with similar symptoms and no clear etiology. The cause of the disease was subsequently identified as a new form of coronavirus called SARS-CoV-2 and the disease was named COVID-19. Historically, Brazil has experienced difficulties with integrated data collection in a national surveillance system. The clinical characteristics and outcomes of COVID-19 hospitalizations are critical to the management of the pandemic. In addition, knowledge of COVID-19 can guide health care management for possible future emergencies. OBJECTIVE: To analyze the clinical and epidemiologic profile of patients diagnosed with COVID-19 and to describe the characteristics of survivors and non-survivors in a cardiopulmonary referral hospital. MATERIALS AND METHODS: This is a descriptive, retrospective, cross-sectional, quantitative study. The study was conducted at the Hospital de Messejana (Fortaleza-Ceará), from October 2021 to May 2022. We included patients of both sexes aged 18 years and confirmed diagnosis ≥ COVID-19, hospitalized between January and June 2021. The information was retrieved through the records in the hospital's electronic medical records. We analyzed 502 electronic records of individuals with a confirmed diagnosis of COVID-19. Excluded were: cases of influenza syndrome without confirmation of SARSCoV-2 infection, individuals transferred to other facilities and therefore without knowledge of clinical outcome, patients with incomplete medical records, and patients hospitalized in low complexity beds. Statistical analysis included Wilcoxon, chi-squared, and Fisher’s exact tests for comparison between groups. Analysis of measures of associations were expressed as relative risk (RR) with 95% confidence intervals (95% CI), and finally survival analysis was performed using the Kaplan-Meier method and the Cox regression model to calculate the crude hazard ratio (HR) with the corresponding 95% CI. RESULTS: The sample consisted mainly of older and male patients (60±14 years). After analysis, it was observed that non-survivors (NS=63%) were older than survivors (NS=63±14 years versus S=55±13 years, p<0.001). At the time of admission, the most common symptoms were dyspnea (87.5%), cough (73.5%), fever (68.3%), and myalgia (33.7%). The mean duration of symptoms before hospitalization was 9.5±6.5 days. The most common comorbidities were systemic arterial hypertension (SAH58.2%), diabetes mellitus (DM-38.4%), smoking (26.9%), obesity (26.1%), nad heart disease (23.7%). In the NS group, SAH (NS=200 vs. S=92; p=0.003) and smoking (NS=99, 31% vs. S=36; p=0.004) were predominant. The S group had a greater use of noninvasive ventilation (NIV) via helmet interface compared to the NS group (S=116, 63%; vs NS=92, 28%; p<0.001). The majority of patients using invasive mechanical ventilation (IMV) progressed to a fatal outcome (n=299, 94%). Of the 502 patients in the study, 63.1% (n=317) of those admitted for severe COVID-19 died in the hospital. Individuals who underwent IMV had a 6.29 increased risk of death compared to those who did not (95% CI 4.08 – 9.71; p< 0.001). For renal replacement therapy (RRT), the risk was 2.25 higher than for those who did not receive RRT (95%CI 1.93-2.62; p< 0.001). In the survival analysis, those who underwent IMV had a 3.3- fold higher mortality compared to those who did not (HR = 3.30; 95%CI (2.04-5.33) p=0.000). Time analysis showed that at 10 days, 20 days and 30 days, the survival rate for those on mechanical ventilation was ±78%, 50% and 28%, respectively. Those who used CRT had a 1.7 times higher mortality compared to those who did not (HR = 1.70; 95% CI (1.35-2.15) p=0.000). CONCLUSION: NS were older, had more comorbidities such as SAH, smoking, longer ICU stay, use of IMV and more complications such as cardiac arrest, acute renal failure and septic shock. Finally, older age, need for IMV and RRT were associated with higher inhospital mortality.